An American romance - Koning, Hans, 1921-2007 (Allison & Busby, 1989)
Koning's novel about two people who get married almost immediately after meeting and falling in love is a crushing story about how two people can live and be in love, not seeing eye to eye. It is about how unhappy lives are lived. I had never read a love story that portrayed love this honestly, but this one really succeeds. Granted, it isn't the story of all loves, but of a failed attempt at it by two people who wanted it to work.